17β-Estradiol attenuates inflammation and tendon degeneration in a rat model of Achilles tendinitis. (4th July 2022) - Wang, Feng; Shan, Haojie; Song, Guoxun; Chen, Song; Zhang, Chengyuan; Liu, Yingjie; Wu, Tianyi
Abstract: Introduction: 17β-Estradiol (E2) is an immune-regulatory agent with anti-inflammatory effects. However, it is still unknown whether E2 exerts pharmacological properties against Achilles tendinitis (AT). This study aims to investigate the effects of E2 on AT and its underlying mechanisms. Materials and Methods: The established model of Achilles tendinitis was intraperitoneally injected with E2 (10, 20, or 30 μg/kg/d). After 8 weeks, biomechanical properties of the Achilles tendon were determined. Hydroxyproline content and tendon degeneration-related biomarkers were determined. The levels of inflammatory cytokines and apoptotic-related biomarkers in tendon tissues were determined. Furthermore, western blotting was determined to detect the expressions of ER-α and the PI3K/Akt pathway in tendon tissues. Results: E2 relieved AT-related symptoms in a dose-dependent manner. E2 ameliorated tendon degeneration by regulating tendon degeneration-related biomarkers (e.g. collagen types I and III, Decorin (DCN), and tenascin-C). Besides, treatment with E2 suppressed inflammatory cytokines and increased anti-inflammatory cytokines. Treatment with E2 also regulated cell apoptosis in tendon tissues. The underlying mechanism study revealed that treatment with E2 activated ER-α and upregulated the PI3K/Akt pathway. Conclusion: The regulatory effects of E2 on inflammation and tendon degeneration in a rat model of AT were associated with the ER-α and the PI3K/Akt signaling pathways.